Targeting of lysosomal-bound protein mEAK-7 for cancer therapy - Chang, Insoon; Loo, Yi-Ling; Patel, Jay; Nguyen, Joe Truong; Kim, Jin Koo; Krebsbach, Paul H. (Frontiers in Oncology, 2024)
mEAK-7 (mammalian EAK-7 or MTOR-associated protein, eak-7 homolog), is an evolutionarily conserved lysosomal membrane protein that is highly expressed in several cancer cells. Multiple recent studies have identified mEAK-7 as a positive activator of mTOR (mammalian/mechanistic target of rapamycin) signaling via an alternative mTOR complex, implying that mEAK-7 plays an important role in the promotion of cancer proliferation and migration. In addition, structural analyses investigating interactions between mEAK-7 and V-ATPase, a protein complex responsible for regulating pH homeostasis in cellular compartments, have suggested that mEAK-7 may contribute to V-ATPase-mediated mTORC1 activation. The C-terminal α-helix of mEAK-7 binds to the D and B subunits of the V-ATPase, creating a pincer-like grip around its B subunit. This binding undergoes partial disruption during ATP hydrolysis, potentially enabling other proteins such as mTOR to bind to the α-helix of mEAK-7. mEAK-7 also promotes chemoresistance and radiation resistance by sustaining DNA damage-mediated mTOR signaling through interactions with DNA-PKcs (DNA-dependent protein kinase catalytic subunit). Taken together, these findings indicate that mEAK-7 may be a promising therapeutic target against tumors. However, the precise molecular mechanisms and signal transduction pathways of mEAK-7 in cancer remain largely unknown, motivating the need for further investigation. Here, we summarize the current known roles of mEAK-7 in normal physiology and cancer development by reviewing the latest studies and discuss potential future developments of mEAK-7 in targeted cancer therapy.